A VIEW ON MILITARY OPERATIONS AGAINST THE ARMED SEPARATISTS IN PAPUA FROM THE STATE POWER PERSPECTIVE - Marjan Miharja; AL-Qamar S. Sangadji (Surakarta Law and Society Journal, 2019)
The ongoing conflict between the armed separatists (OPM) in Papua and the Indonesian government is a domestic disorder, friction, and disturbance which can endanger the state sovereignty, territorial integrity of the state, and the safety of the entire nation. If this situation is not handled seriously, it can develop into a permanent condition which surely can turn into a major threat for the national security. Currently, the government has conducted military operations to deal with the OPM rebellion. The research problem is to describe the use of military operations within the state power perspective; and whether the use of military operations against the armed separatists in Papua has already been in accordance with the state power principle. This present research is a normative juridical method within a qualitative approach in which the data are analyzed by using the interpretive method. It is also a descriptive-analytical research in which it describes the applicable legislation and relates it with legal theories and the implementation practices of the positive laws which are related to the research problem. By using a library research, the data related to the research problems, e.g. written legislation, conventions, agreements, theses, journals, and other documents from the legal experts, were collected and analyzed